Teachers' Multifaceted Roles in Enhancing Learning Motivation: A Qualitative Study of Fifth-Grade Elementary Students in Indonesia - Khuzaimah, Ade; Gagaramusu, Yusdin Bin. M; Nashrullah, Nashrullah; Zulnuraini, Zulnuraini; Khairunnisa, Khairunnisa (Journal of Innovation and Research in Primary Education, 2025)
Teachers play crucial roles in enhancing elementary students' learning motivation, yet limited empirical evidence exists regarding practical implementation of motivational strategies in specific classroom contexts. This qualitative descriptive study investigated teachers' roles in enhancing learning motivation among fifth-grade students at SD Inpres 1 Kawatuna, Palu City, Indonesia. Data were collected through classroom observations, semi-structured teacher interviews, and student questionnaires (N=26) during the 2024/2025 academic year. Thematic analysis of qualitative data and descriptive statistics of quantitative data were employed. Findings revealed that teachers enacted five interconnected roles: inspirator (providing learning strategy guidance), motivator (offering positive reinforcement and rewards), facilitator (accommodating diverse learning styles), guide (delivering individualized support), and classroom manager (creating conducive environments). These practices resulted in 88.46% of students demonstrating good to excellent motivation levels across six indicators: persistence in completing tasks, resilience in facing difficulties, interest in diverse problems, preference for independent work, resistance to boredom, and ability to maintain opinions. However, 11.53% of students exhibited only fair motivation, particularly in autonomous learning behaviors. The study contributes by bridging theory-practice gaps in motivation literature and documenting context-specific implementations of motivational principles. Implications include emphasizing comprehensive teacher role training in professional development programs and conducting longitudinal research examining long-term motivational development.